PURTSCHER'S‒LIKE RETINOPATHY SECONDARY TO GRANULOMATOSIS WITH POLYANGIITIS FOLLOWING AUTOLOGOUS STEM CELL TRANSPLANTATION. Issue Volume 16:Issues 4(2022) (23rd April 2020) - Hupy, Matthew L.; Pecen, Paula E.; Kolfenbach, Jason R.; Lau, Marissa; Palestine, Alan G.
Abstract : A 25-year-old man underwent an autologous stem cell transplant regiment for a nongermanomatous germ cell brain tumor and subsequently developed granulomatosis with polyangiitis and Purtscher's‒like retinopathy. Abstract : Purpose: The authors describe a man undergoing autologous stem cell transplant, who developed granulomatosis with polyangiitis and Purtscher's‒like retinopathy. Methods: A 25-year-old man underwent fundus photography, optical coherence tomography, and fluorescein angiography to obtain a diagnosis and follow the treatment course. Results: The initial ophthalmic presentation and imaging confirmed the findings of Purtscher's‒like retinopathy. Throughout his course, he had progressive neovascularization and vitreous hemorrhages in both eyes, requiring vitrectomy and endolaser, and bevacizumab injections. Conclusion: The authors describe a patient who underwent autologous stem cell transplantation, and subsequently developed granulomatosis with polyangiitis. The presentation of Purtscher's‒like retinopathy suggests that microvascular occlusion in the retina was likely the result of granulomatosis with polyangiitis-driven vasculitis of the precapillary arterioles.